Impact of manager characteristics on the agricultural business success - Negrão, Carla Sofia Vicente (Conferência - Investigação e Intervenção em Recursos Humanos, 2018)
In an increasingly digital and competitive environment for entreprises, it becomes a challenge for the management of agricultural enterprises to achieve success, whether the company uses e-business or not. An individual approach that helps explain the agricultural business success through manager characteristics is developed in this research. Characteristics of managers are considered importante because it is they who make the strategic decisions of the agricultural enterprises. The main objective of this research is to analyze the impact of manager characteristics on agricultural business success, in Portugal in 2014. In order to reach the objective of the paper a concetual model of success of the agricultural companies is developed, whether you use e-business or not. Subsequently, through a quantitative approach, collected by questionnaire and a sample consisting of 416 agricultural enterprises is obtained, constituted by entreprises that use or not e-business. For empirically test the hypotheses of research, econometric analyse is used through hierarchical regression. The empirical results suggest that increasing the age of agricultural managers reduces the agricultural business success, however, the results were inconclusive for the education of managers. The size of the entreprises, measured by the number of employees, has a positive influence on agricultural business success. In addition, entreprises belonging to a group are more successful than others. We present the limitations of this investigation and suggest future research. Although business success is a subject discussed in the literature, the agricultural business success is still not clearly developed and is central to the national economy. At the time of data collection, Portugal was experiencing a serious economic crisis and the agricultural business success can boost potential economic growth. Although this study is not conclusive regarding the education of the managers, it contributes to the addition of the theory of success of agricultural enterprises, based on a holistic approach.